2022
DOI: 10.3390/life12060885
|View full text |Cite
|
Sign up to set email alerts
|

cAMP Is a Promising Regulatory Molecule for Plant Adaptation to Heat Stress

Abstract: With gradual warming or increased frequency and magnitude of high temperature, heat stress adversely affects plant growth and eventually reduces plant productivity and quality. Plants have evolved complex mechanisms to sense and respond to heat stress which are crucial to avoiding cell damage and maintaining cellular homeostasis. Recently, 33″,55″-cyclic adenosine monophosphate (cAMP) has been proved to be an important signaling molecule participating in plant adaptation to heat stress by affecting multi-level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…APT activity in recycling nucleoside in the salvage pathway also enables it to regulate the flux of the nucleotide degradation pathway [ 40 ]. AMP plays an important role in mediating stress by altering plant hormone homeostasis and energy metabolites [ 41 ]. Additionally, alterations in adenine at the cellular level can trigger tolerance and promote growth [ 42 ], and purine recycling pathways can play the role of cellular signaling molecules in regulating plant responses to abiotic stresses [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…APT activity in recycling nucleoside in the salvage pathway also enables it to regulate the flux of the nucleotide degradation pathway [ 40 ]. AMP plays an important role in mediating stress by altering plant hormone homeostasis and energy metabolites [ 41 ]. Additionally, alterations in adenine at the cellular level can trigger tolerance and promote growth [ 42 ], and purine recycling pathways can play the role of cellular signaling molecules in regulating plant responses to abiotic stresses [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, genes associated with Golgi vesicle transport and resistance to ROS were commonly upregulated in these conditions (Supplementary Data 4). Previous researches demonstrated that the addition of cAMP can enhance the expression of genes involved in vesicle transport at high temperatures 27 and boost cellular resistance to ROS 28 . Therefore, it is possible that YKL069W mediate the pulsatile increase in cAMP levels, leading to the upregulation of vesicle transport genes and anti-ROS genes.…”
Section: Cyr1 Mutation Modulates the Camp Signaling Pathway To Rebuil...mentioning
confidence: 99%
“…NO bursting at the apex of shoots under heat stress conditions triggers whole‐plant cellular responses to high temperatures and S‐nitrosylates a trihelix transcription factor GT‐1, thus enhancing its binding to NO‐responsive elements in the HSFA2 promoter and downstream gene expression in Arabidopsis (He et al, 2022). As a signalling molecule, 3ʹ,5ʹ‐cyclic adenosine monophosphate (cAMP) affects multiple levels of regulatory networks in plants to combat heat stress (Liang et al, 2022). However, how these two signalling molecules function in rice is unknown.…”
Section: Heat Stress Sensing and Signallingmentioning
confidence: 99%